SB203580 increases G-CSF production via a stem-loop destabilizing element in the 3' untranslated region in macrophages independently of its effect on p38 MAPK activity. Issue 1 (December 2016) - Chang, Shwu-Fen; Li, Huai-Ci; Huang, Yu-Pei; Tasi, Wen-Ju; Chou, Yuan-Yi; Lu, Shao-Chun
Abstract Background Granulocyte-colony stimulating factor (G-CSF) is a major regulator of the production and survival of neutrophils. Regulation of G-CSF expression is complex and occurs at both transcription and post-transcription levels. Two distinct types of cis-acting elements in the 3' untranslated region (3'UTR) of G-CSF mRNA have been identified as destabilizing elements; these consist of adenylate uridylate-rich elements (AUREs) and a stem–loop destabilizing element (SLDE). Regulation of the stability of mRNA by p38 mitogen-activated protein kinase (MAPK) has been indicated to be linked to AUREs in the 3'UTR. However, whether p38 MAPK is involved in the regulation of the stability of G-CSF mRNA has not been elucidated. This study investigated the effect of SB203580, an inhibitor of p38 MAPK, on the lipopolysaccharide-induced G-CSF expression in macrophages at the post-transcription level. Results Our study showed surprising results that SB203580 augmented the lipopolysaccharide-induced increase in the G-CSF mRNA levels in RAW264.7 mouse macrophages, mouse bone marrow-derived macrophages and in THP-1 human macrophages. This effect was also seen in p38α MAPK knockdown RAW264.7 cells, showing that it was not due to inhibition of p38 MAPK activity. In the presence of actinomycin D, the decay of G-CSF mRNA was slower in SB203580-treated cells than in control cells, showing that SB203580 increased the stability of G-CSF mRNA. Reporter genes containing luciferase with or without the 3'UTR of G-CSF were constructed and transfected into RAW264.7 cells and the results showed that the presence of the 3'UTR reduced the luciferase mRNA levels and luciferase activity. Furthermore, SB203580 increased the luciferase mRNA levels and activity in RAW264.7 cells transfected with the luciferase reporter containing the 3'UTR, but not in cells transfected with the luciferase reporter without the 3'UTR. Mutations of the highly conserved SLDE in the 3'UTR abolished these effects, showing that the SLDE was essential for the SB203580-induced increase in the stability of mRNA. Conclusions SB203580 increases G-CSF expression in macrophages by increasing the stability of G-CSF mRNA via its 3'UTR, and the effect was not due to its inhibition of p38 MAPK activity. The results of this study also highlight a potential target for boosting endogenous production of G-CSF during neutropenia.